Evaluasi Kinerja Sistem Drainase Di Wilayah Nganjuk: How to Evaluate Drainage Performance - MUHAMMAD BURHANUL MAJID Burhan (Universitas Pancasakti Tegal, 2024)
This study aims to identify the factors causing flooding and formulate solutions to improve the performance of the drainage system in Salamrojo Village, Nganjuk. The methods used include hydrological analysis by collecting rainfall data for the last ten years and calculating flood discharge using the Rational Formula. The results of the study indicate that the water runoff discharge exceeds the capacity of the existing drainage channels, causing flooding that damages infrastructure. The current condition of the drainage channel with a storage discharge of 0.0739 m³/sec, is unable to accommodate the water runoff discharge at a two-year return period of 0.1330 m³/sec. Therefore, it is recommended to improve the dimensions of the drainage channel from B = 0.5 m and H = 0.3 m to B = 0.7 m and H = 0.4 m to increase the storage capacity. This study is significant in providing recommendations for improving the drainage system and is expected to encourage the implementation of environmentally friendly drainage to reduce the risk of flooding in the future.